The relationship between emotional intelligence and job performance: a case of O&G industry in Malaysia - Hamizat, Nurul Hazirah (2021)
Emotional Intelligence (EI) plays a vital role in Job Performance (JP), especially in avoiding turnover issue due to psychological distress in the workplace. This study examines the relationship between EI and JP of employees in the Oil and Gas (O&G) industry in Malaysia to determine its relationship as well as the demographics effect on these two components. Thus, three pioneering models of EI have been identified and Mixed Model introduced by Goleman was chosen and applied in this study. Two hypotheses have been proposed based on the conceptual. Concurrently, self-report survey questionnaires were distributed through a Google Forms to test the significance between these two components, EI and JP. Data were obtained from 103 staffs of one O&G company in Malaysia with an 84% response rate. Based on the findings, there is a significant relationship between EI and JP where the results align with some prior research. However, there is a lack of evidence to support the idea that demographics have significant effect on these components. Therefore, further research is recommended to identify other significant components that can improve EI and JP levels. Nonetheless, the results from these obtained data suggest the need to implement this framework to determine EI’s level of the employees to strengthen the EI and enhance their JP. In view of the fact that by enhancing the EI it can affect the JP, and as a result, it contributes to organizational and management effectiveness to both industry practitioners and the academicians.